Does agri-environmental management enhance biodiversity and multiple ecosystem services?: A farm-scale experiment - Bullock, James M.; McCracken, Morag E.; Bowes, Michael J.; Chapman, Roselle E.; Graves, Anil; Hinsley, Shelley A.; Hutchins, Michael G.; Nowakowski, Marek; Nicholls, David J. E.; Oakley, Simon; Old, Gareth H.; Ostle, Nicholas J.; et al. (Elsevier, 2021)
Agri-environmental management has been promoted as an approach to enhance delivery of multiple ecosystem services. Most agri-environment agreements include several actions that the farmer agrees to put in place. But, most studies have only considered how individual agri-environmental actions affect particular ecosystem services. Thus, there is little understanding of how the range of agri-environmental actions available to a farmer might be deployed on any individual farm to enhance multiple services. To address this knowledge gap, we carried out an experimental study in which we deployed a set of agri-environmental actions on a commercial farm in southern England. Agri-environmental actions comprised wildflower margins and fallow areas in arable fields, creating and enhancing grassland with wildflowers, and digging ponds. Alongside biodiversity responses, we measured effects on a number of ecosystem services: pollination, pest control, crop and forage yield, water quality, climate regulation and cultural services. Wildflower margins enhanced invertebrates, pest control and crop yield, and aesthetic appeal. A greater number of pollinators was linked to enhanced oilseed rape yield. But these margins and the fallows did not prevent run-off of nutrients and sediment into waterways, and showed limited carbon sequestration or reduction of greenhouse gas emissions. Newly-dug ponds captured large amounts of sediment and provided aesthetic appeal. Grasslands had higher soil carbon content and microbial biomass, lower N20 emissions, and net sequestration of carbon compared to arable land. Enhancement of grassland plant diversity increased forage quality and aesthetic appeal. Visitors and residents valued a range of agri-environmental features and biodiversity across the farm. Our findings suggest one cannot necessarily expect any particular agri-environmental action will enhance all of a hoped-for set of ecosystem services in any particular setting. A bet-hedging strategy would be for farmers to apply a suite of options to deliver a range of ecosystem service benefits, rather than assuming that one or two options will work as catch-all solutions.
Keywords: Carbon sequestration; Cultural services; Greenhouse gases; Pest control; Pollination; Water quality